Organizational Conflict Management in Library Teams: A Multisite Case Study in Islamic Schools - Chasan Maruf; Ach. Baidowi; Mahamadaree Waeno; Abdullah Ibrahim (International Journal of Educational Narratives, 2026)
Background. This study examines errors in organizational conflict management within library settings that lead to stress, decreased motivation, poor communication, and inefficiency in library team performance. Purpose. The aim of this research is to identify the forms and sources of conflict, describe conflict management strategies, and analyze their impact on the performance of Islamic school library teams in a multisite context. Methods. This study uses a qualitative approach with a multisite case study design at Sekolah Dasar Islam Terpadu Yaa Bunayya and Ma’had Badr, employing data collection techniques including interviews, observation, and documentation, followed by data condensation analysis, data presentation, conclusion drawing, and data triangulation. Results. The findings show that conflicts arise from differences in book management, work coordination, and staff responsibilities. In Sekolah Dasar Islam Terpadu Yaa Bunayya, issues include damaged books, a lack of SOPs, and differing perceptions between the library head and homeroom teachers. Conflict resolution strategies involve persuasive communication, clarification, discussion, and clearer task distribution. The impact includes improved communication, greater responsibility, and greater service stability, although disciplinary variations still persist. In Ma’had Badr, conflicts are triggered by staff absenteeism, weak shift coordination, and varying work abilities, and are resolved through discussion and collective agreements grounded in organizational values. Conclusions. The conclusion indicates that conflict management through communication and deliberation improves team performance, although coordination differences persist and remain effectively addressed.